2019
DOI: 10.1021/acsami.9b11012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive, Superhigh Signal-to-Noise Ratio, Self-Powered Solar-Blind Photodetector Based on n-Ga2O3/p-CuSCN Core–Shell Microwire Heterojunction

Abstract: Solar-blind photodetectors have captured intense attention due to their high significance in ultraviolet astronomy and biological detection. However, most of the solar-blind photodetectors have not shown extraordinary advantages in weak light signal detection because the forewarning of low-dose deep-ultraviolet radiation is so important for the human immune system. In this study, a high-performance solar-blind photodetector is constructed based on the n-Ga2O3/p-CuSCN core–shell microwire heterojunction by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(95 citation statements)
references
References 70 publications
4
90
0
1
Order By: Relevance
“…The ZCR device has a signicantly higher responsive current than the ZC device. The signal-tonoise ratio (i.e., SNR ¼ (I l À I d )/I d , where I l is the photocurrent under 365 nm light illumination and I d is the dark current given above) 69 also increases from 2.2 Â 10 3 (ZC) to 3.6 Â 10 3 (ZCR), which is consistent with the calculation of the detectivity. Moreover, the response time is another important indicator for photodetector performance, including the rise time s r and the fall time s f , 70 as shown in Fig.…”
Section: Nepsupporting
confidence: 87%
“…The ZCR device has a signicantly higher responsive current than the ZC device. The signal-tonoise ratio (i.e., SNR ¼ (I l À I d )/I d , where I l is the photocurrent under 365 nm light illumination and I d is the dark current given above) 69 also increases from 2.2 Â 10 3 (ZC) to 3.6 Â 10 3 (ZCR), which is consistent with the calculation of the detectivity. Moreover, the response time is another important indicator for photodetector performance, including the rise time s r and the fall time s f , 70 as shown in Fig.…”
Section: Nepsupporting
confidence: 87%
“…i,j) Reproduced with permission. [219] Copyright 2019, American Chemical Society. Monolayer graphene/ freshly cleaved (100) 6 shows the device performance and the built-in voltage for the different gallium oxide based PDs showing self-powered behavior.…”
Section: Self-powered Pds Based On Gallium Oxidementioning
confidence: 99%
“…To improve the performance of PDs, Li et al suggested the combination of β-Ga 2 O 3 with hole transport materials such as inorganic copper-based hole transport materials including Cu 2 O, CuI, CuSCN, CuCrO 2 and CuGaO 2 , and organic hole transport materials such as PEDOT:PSS and spiro-MeOTAD, to form a heterojunction with β-Ga 2 O 3 . 148 The SB PD based on the n-Ga 2 O 3 /p-CuSCN core–shell microwire heterojunction demonstrated a responsivity of 13.3 mA W −1 , photo-to-dark current ratio of 4.14 × 10 4 , UV/visible rejection ratio of 1.15 × 10 4 and detectivity of 9.43 × 10 11 Jones under a bias of 5 V. 149 Further, Li et al 150 reported a self-powered PEDOT:PSS/Ga 2 O 3 hybrid heterojunction SB photodetector with a responsivity of 37.4 mA W −1 and detectivity of 9.2 × 10 12 Jones. The device also exhibited an EQE of 18.3% at 254 nm, which is attributed to the efficient separation of photogenerated electron–hole pairs caused by the built-in electric field and the large photovoltaic effect of the PEDOT:PSS/Ga 2 O 3 heterojunction.…”
Section: Ga2o3 Materialsmentioning
confidence: 99%